Wearing a surgical mask does not affect the anaerobic threshold during pedaling exercise - Otsuka, A.; Komagata, J.; Sakamoto, Y. (Journal of Human Sport & Exercise, 2022)
The effect of wearing a surgical mask on cardiopulmonary function and anaerobic threshold (AT) has not been reported. Thus, we aimed to determine whether cardiopulmonary function and AT vary while wearing surgical masks. Six healthy men were enrolled and underwent the cardiopulmonary exercise (CPX) stress test under two different conditions (with and without a commercially available surgical mask) to evaluate their AT. To confirm that there was no breath leakage, a gas mask connected with a respiratory gas analyser was worn over the surgical mask when the participants performed the CPX. The AT was measured by the V-slope method. Moreover, the AT time, exercise load, oxygen consumption, and ventilation values after the CPX were determined. No significant differences were found between the two conditions. The number of complaints of respiratory distress, however, was significantly higher while wearing a surgical mask. The exercise intensity achieved by each participant was equivalent, irrespective of whether they wore the surgical mask; therefore, wearing a surgical mask does not affect cardiopulmonary function during vigorous exercise.